Studying Generation Z's Saving Interest: Sharia Financial Literacy, Religius, and Lifestyle - Irdiana, Sukma; Darmawan, Kusnanto; Jariah, Ainun (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to investigate the factors that influence Generation Z's interest in saving at Islamic banks. Generation Z, born between the mid-1990s to the early 2010s, has been in the spotlight for their unique financial behavior and tendency to use technology in their financial transactions. In this context, Islamic financial literacy, religiosity, and lifestyle are considered as key factors that might influence their interest in saving in Islamic banks. This research uses a quantitative approach, using a simple random sampling method in taking samples. The number of samples in this research was 80 generation Z in Lumajang Regency. The analysis technique used is multiple linear regression analysis. The results of this research show that sharia financial literacy and religiosity have a significant effect on generation Z's interest in saving at sharia banks. However, lifestyle does not have a significant effect on generation Z's interest in saving at Sharia Banks. The coefficient of determination in this study was 79%, this shows that sharia financial literacy and religiosity have an important role in generation Z's interest in saving at Sharia Banks in Lumajang Regency. Meanwhile, Generation Z's lifestyle does not prevent them from saving at Sharia Bank.